2019
DOI: 10.1021/acsomega.9b00431
|View full text |Cite
|
Sign up to set email alerts
|

Function of Tetrabutylammonium on High-Efficiency Ruthenium Sensitizers for Both Outdoor and Indoor DSC Application

Abstract: The function of tetrabutyl ammonium ions (TBA + ) in a sensitizer used in dye-sensitized solar cells (DSC) is contradictory. TBA + can reduce unwanted charge-recombination by protecting the TiO 2 surface and reduce dye aggregation, enhancing the photovoltaic performance. It will also compete with the dye-loading on the TiO 2 film, decreasing the short-circuit current density of the cell. Three ruthenium sensitizers (DYE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The heteroleptic Ru complex was prepared with the one-pot reaction protocol similar to our previous report . 0.337 g (0.55 mmol) of [RuCl 2 ( p -cymene)] 2 and 0.736 g (1.10 mmol) of ancillary ligand bearing two 2-thiohexyl-3,4-ethylenedioxy-thiophene (TH-EDOT) units (L20) were prepared according to the literature; 0.692 g (1.10 mmol) of L22-ester and excess ammonium thiocyanate (NH 4 NCS) were added in a Schlenk flask containing DMF and then hydrolyzed with 0.115 g (2.75 mmol) LiOH·H 2 O in water. After refluxing for 12 h, dilute HNO 3(aq.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heteroleptic Ru complex was prepared with the one-pot reaction protocol similar to our previous report . 0.337 g (0.55 mmol) of [RuCl 2 ( p -cymene)] 2 and 0.736 g (1.10 mmol) of ancillary ligand bearing two 2-thiohexyl-3,4-ethylenedioxy-thiophene (TH-EDOT) units (L20) were prepared according to the literature; 0.692 g (1.10 mmol) of L22-ester and excess ammonium thiocyanate (NH 4 NCS) were added in a Schlenk flask containing DMF and then hydrolyzed with 0.115 g (2.75 mmol) LiOH·H 2 O in water. After refluxing for 12 h, dilute HNO 3(aq.)…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that the device sensitized with CYC-B22 displays a panchromatic response extending to 850 nm, which is broader than those of the cells based on CYC-B23C, CYC-B23T, N719, and the other bipyridyl heteroleptic Ru complexes using dcbpy anchoring ligand. 1,2,15,16,[30][31][32][33][34][35][36]47 Evidently, the highest J sc and PCE of CYC-B22-sensitized device are ascribed to the best light-harvesting capability provided by the highly conjugated anchoring and ancillary ligands as well as the highest amount of dye-loading (77.8 nmol cm −2 in Table 2) for the largest light-harvesting efficiency 17 (LHE; Figure S7). Surprisingly, the PCE of the CYC-B23T-sensitized device is comparable with that of the CYC-B22-based cell but remarkably higher than those of cells dyed with its stereoisomer (CYC-B23C).…”
Section: Photovoltaic Performance Of Devicesmentioning
confidence: 97%
“…Using TBA + to replace H + has the advantages of increasing the solubility of the sensitizer, at the same time, to avoid the protonation of TiO 2 to lower its Fermi level and therefore to reduce the theoretic open-circuit voltage (V OC ) when the dye molecules adsorbed on TiO 2 anode. [9] Z-907 dye [10] (its structure see Figure 1) is also a representative [2211] ruthenium dye reported by Grätzel et al They used two hydrophobic nonyl groups to replace two carbonylate groups in one of the bidentate anchoring ligand of N3 dye to increase the hydrophobility of the dye molecules. The PCE of Z-907 dyed DSC is only 6.6%, nevertheless, DSC based on Z907 dye reveals good longterm stability.…”
Section: [2211] Ruthenium Dyesmentioning
confidence: 99%
“…Nguyen et al studied a Ru dye and the effect that tetrabutylammonium cations (as a salt on the COO − anchoring group before attachment on titania) have on cell efficiency when they replace the protons of the carboxylic groups. 45 The larger cation, in fact, can help to protect the TiO 2 surface and reduce dye aggregation, but at the same time it will reduce dye loading. They found that adding a single tetrabutylammonium cation to the dye gives the best results, with device efficiencies varying between 14% at 363 lx and 32% at 6372 lx.…”
Section: Dye-sensitized Solar Cells: Materials and Devicesmentioning
confidence: 99%